Identifying training needs of practising community pharmacists in Jordan-a self-assessment study - Saja A. Alnahar; Rula M. Darwish; Shatha Z. Al Qasas; Mayada M. Al Shabani; Ian Bates (BMC, 2024)
Abstract Background Being the professional membership body for pharmacists in Jordan, the Jordan Pharmacists Association (JPA) took the initiative to establish a training centre for practising pharmacists. This study aims to identify the self-assessed training priorities of community pharmacists in Jordan. Methods In the period between August and October 2022, an online self-administered questionnaire was distributed using a variety of participants' identification and recruitment approaches. The questionnaire targeted currently practising community pharmacists. Data were analysed descriptively and inferentially. Results In total, 470 community pharmacists participated in this study. Of 470 participants, 307 (65.3%) were employees, of which 206 were full-time employees. Results showed that only 97 (21%) had access to an in-house training programme or scheme. Self-assessment of training needs highlighted differences between the three competencies clusters. While administrative and managerial skills and competencies were more frequently prioritised on average than the other two clusters, interpersonal and communication skills were needed the least. Evidence showed a significant difference between female and male participants regarding the need for training addressing maternity and early childhood health training issues. Lastly, the role-based comparison showed that, compared to pharmacy owners, employees had a significantly higher need for training related to bookkeeping and taxation returns preparation and how to handle and manage records of narcotic and controlled medicines. Conclusions If training and development programmes are tailored to address specific needs in administrative, clinical, and interpersonal competencies, community pharmacists have the potential to enhance public health, expand their role, provide patient-centred care, and support the national healthcare system.